2019
DOI: 10.1111/ajag.12672
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Malay Version of the De Jong Gierveld Loneliness Scale

Abstract: Objective This study aims to determine the psychometric properties of the Bahasa Malaysia (BM) version of the 6‐item De Jong Gierveld Loneliness Scale (DJGLS) among older adults in Malaysia. Methods A total of 200 participants aged 50 years and older completed the questionnaire in which 81 participants completed in BM. A subsample of 30 participants was retested after a period of 2 weeks. Results The DJGLS showed good internal consistency (Cronbach's alpha 0.71) and high test‐retest reliability (r = 0.93). Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Fourteen validations of some of the versions of the De Jong Gierveld Loneliness Scale (DJGLS; De Jong-Gierveld and Kamphuls, 1985 ) were carried out; specifically, eight validations of the 6-item DJGLS ( Leung et al, 2008 ; De Jong Gierveld and Van Tilburg, 2010 ; Ayala et al, 2012 ; Iecovich, 2013 ; Cheung et al, 2020 ; Hosseinabadi et al, 2020 ; Jaafar et al, 2020 ; Rodríguez-Blázquez et al, 2021 ) and six validations of the 11-item DJGLS ( Buz and Pérez-Arechaederra, 2014 ; Penning et al, 2014 ; Tomás et al, 2017 ; Uysal-Bozkir et al, 2017 ; Caycho-Rodríguez et al, 2021 ; Hosseinabadi et al, 2021 ). In the study by De Jong Gierveld and Van Tilburg (2010) , the validated emotional DJGLS-3 and social DJGLS-3 scales are equivalent to the DJGLS-6 scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen validations of some of the versions of the De Jong Gierveld Loneliness Scale (DJGLS; De Jong-Gierveld and Kamphuls, 1985 ) were carried out; specifically, eight validations of the 6-item DJGLS ( Leung et al, 2008 ; De Jong Gierveld and Van Tilburg, 2010 ; Ayala et al, 2012 ; Iecovich, 2013 ; Cheung et al, 2020 ; Hosseinabadi et al, 2020 ; Jaafar et al, 2020 ; Rodríguez-Blázquez et al, 2021 ) and six validations of the 11-item DJGLS ( Buz and Pérez-Arechaederra, 2014 ; Penning et al, 2014 ; Tomás et al, 2017 ; Uysal-Bozkir et al, 2017 ; Caycho-Rodríguez et al, 2021 ; Hosseinabadi et al, 2021 ). In the study by De Jong Gierveld and Van Tilburg (2010) , the validated emotional DJGLS-3 and social DJGLS-3 scales are equivalent to the DJGLS-6 scale.…”
Section: Resultsmentioning
confidence: 99%
“…The intraclass correlation coefficient (ICC) was reported in the studies by Leung et al (2008) , Neto (2014) , and Hosseinabadi et al (2020) and test–retest reliability measures in the work by Jaafar et al (2020) .…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the shortened scale produced both valid and reliable scores for overall loneliness and the two subscales. They also reported that the scale works suitably for use in large surveys and has been validated in Chinese (Leung et al, 2008) German, Russian, Bulgarian, Georgian, Japanese, French (all countries included in de Jong Gierveld & Van Tilburg, 2010) and Malaysian (Jaafar et al, 2020). However, although the shortened scale has gained more popularity in recent times, when compared to the original 11-item scale, research concerning the scale's factor structure is concerningly limited.…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is profoundly influenced by socio-cultural factors, and therefore, it is crucial to study loneliness within specific social settings. 4 Out of the 100 million older adults in India, about 75% of them reside in rural areas. 5 Rural areas are characterised by poverty and lack of formal support systems such as access to health care.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its prevalence and adverse consequences, limited emphasis has been placed on understanding the socio‐demographic‐, health‐ or family‐related risks for loneliness, especially in rural communities. Loneliness is profoundly influenced by socio‐cultural factors, and therefore, it is crucial to study loneliness within specific social settings 4 . Out of the 100 million older adults in India, about 75% of them reside in rural areas 5 .…”
Section: Introductionmentioning
confidence: 99%